2011
DOI: 10.1186/1471-2474-12-205
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of neck/shoulder exercises for pain relief among industrial workers: A randomized controlled trial

Abstract: Background: Although leisure-time physical activity is important for health, adherence to regular exercise is challenging for many adults. The workplace may provide an optimal setting to reach a large proportion of the adult population needing regular physical exercise. This study evaluates the effect of implementing strength training at the workplace on non-specific neck and shoulder pain among industrial workers. Methods: Cluster-randomized controlled trial involving 537 adults from occupations with high pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 31 publications
10
169
2
9
Order By: Relevance
“…Evidence increasingly supports the positive effects of staying active instead of bed rest in the treatment of MSD and associated disability (3,4).…”
mentioning
confidence: 99%
“…Evidence increasingly supports the positive effects of staying active instead of bed rest in the treatment of MSD and associated disability (3,4).…”
mentioning
confidence: 99%
“…Strength training relying on principles of progressive overload implemented in workers also reduces neck and shoulder pain (Zebis et al, 2011). Sundstrup et al (Sundstrup et al, 2013 demonstrated that workplace initiatives reduce musculoskeletal pain among employees who perform repetitive and forceful work with their arms, shoulders and hands.…”
Section: Discussionmentioning
confidence: 99%
“…WHP programs include employee education, modified workspace designs, adjusting work habits and promoting exercise, stretches and short rest breaks. The physiologic benefits of a stretch break program include reduced intervertebral disc pressure, increased blood flow, reductions in muscle lactic acid and increased attention (Andersen et al, 2012;Balci & Aghazadeh, 2003;Cheema et al, 2013;Varatharajan et al, 2014;Zebis et al, 2011).…”
Section: Original Article (Full Paper)mentioning
confidence: 99%
“…21 Trening snage u trajanju od 20 tjedana, jedan sat tjedno, znatno smanjuje bol kod že-na u uredu 19 ili muškaraca u industriji. 3 Učestalo se bol u mišiću liječi vježbama snage okolnih, nebolnih mišića, a dokazano je i da jaki trening snage na bolnom miši-ću u vratu dovodi do smanjenja boli. 22 Isti tretman ne djeluje na žene, odnosno navedena je mogućnost nastanka komplikacija kod sudionica.…”
Section: Sudioniciunclassified